Chin-throat morphology of Nepalese adults with normal occlusion and aesthetic facial profile – a cephalometric study - Mahto, Ravi Kumar; Kafle, Dashrath; Rai, Diwash; Sakha, Rabina; Rajbhandari, Nikita (Orthodontic Journal of Nepal, 2022)
Objective(s): The present study was undertaken to obtain normative value for chin-throat morphology in Nepalese adult male and female adult subjects with normal occlusion and aesthetic facial profile and study variation of chinthroat morphology between the two sexes. Materials and Method: In this cross-sectional study, lateral cephalograms of adult subjects with normal occlusion and pleasing facial profiles were selected from the archives of the Department of Orthodontics, Dhulikhel Hospital, Kathmandu University School of Medical Sciences, Nepal. Manual tracing and measurement of 3 parameters evaluating chin-throat morphology i.e. lip-chin-throat angle, chin-throat length and chin-throat-neck angle were done. Descriptive analysis was carried out and Student’s t-test was used to find the difference in measurements between the male and female subjects. Result: The mean values of lip-chin-throat angle, chin-throat length and chin-throat-neck angle were 105.56 ± 8.69 degrees, 40.48 ± 5.95 mm and 121.69 ± 13.86 degrees respectively. The mean value of the lip-chin-throat angle was 106.09 ± 8.60 degrees in male subjects and 105.12 ± 8.92 degrees in female subjects. Similarly, the mean value of chin-throat length was 40.08 ± 5.39 mm for males and 40.80 ± 6.47 mm for females. Also, the mean value of the chinthroat-neck angle was found to be 121.14 ± 16.99 degrees for males and 122.16 ± 10.92 degrees for females. Conclusion: Normative values for chin-throat morphology of Nepalese adults were established. In addition to it, sexual dimorphism was observed for chin-throat morphology while comparing the mean values for male and female subjects. However, the differences were statistically insignificant.